2020
DOI: 10.3390/agronomy10091313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Doses of Methyl Benzoate on the Life History Traits and Acetylcholinesterase (AChE) Activity of Aphis gossypii

Abstract: Safer alternatives to synthetic pesticides are essential for sustainable agriculture. Methyl benzoate (MB) is a volatile essential oil found in several plants. Recent reports of the toxicity of MB to arthropod pests suggest that MB may be a useful alternative insecticide. The present study assessed the effects of a sublethal concentration of MB (LC30, 0.22%) on the life history and reproductive characteristics of the cotton aphid, Aphis gossypii Glover, in both a treated parental generation (F0) and untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Biopesticides (natural products) have emerged as a better alternative for pest control [31]. CucB and EGCG are the major secondary metabolites of host plants cucurbits and cotton, which are the host plant of two typical biotypes of the notorious agricultural pest aphid-CU and CO [14,15,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopesticides (natural products) have emerged as a better alternative for pest control [31]. CucB and EGCG are the major secondary metabolites of host plants cucurbits and cotton, which are the host plant of two typical biotypes of the notorious agricultural pest aphid-CU and CO [14,15,38].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG strongly and directly inhibits telomerase [24] and affects metabolism in mammals and insects [25,26]. Cytochrome P450 monooxygenases (P450s), glutathione S-transferases (GSTs), carboxylesterase (CarE), acetylcholinesterase (AchE), and acid phosphatase (ACP) are involved in xenobiotic metabolism of insects [27][28][29][30][31]. However, the effects of CucB and EGCG on population-level fitness and xenobiotic metabolism enzymes of cotton-melon aphids have never been adequately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MBe exhibited hydrophobic interactions with at least five AChE amino acids [122]. These results suggest that MBe is potentially targeting AChE at a molecular level.…”
Section: Lack Of Knowledge Of Molecular Target(s) and The Mode Of Act...mentioning
confidence: 80%
“…Recently, Feng and Zhang [14] revealed that MBe had a significant impact on D. suzukii development. Mostafiz et al [122] found that a sublethal dose of MBe (LC 30 = 0.22%) significantly reduced the fecundity and longevity of the aphid A. gossypii in the treated parental generation (F0) and their untreated progeny (F1). Moreover, MBe prolonged the developmental duration of each immature instar of the F1 generation compared with the controls.…”
Section: Sublethal Effects Of Methyl Benzoatementioning
confidence: 99%
See 1 more Smart Citation